Study of technical and economical alternatives of a shoring and striking process during the construction of a building with reinforced concrete slab floors - Gasch, I.; Alvarado, Y.; Calderón, P.; Torres, B. (Revista Ingeniería de Construcción, 2016)
The aim of this paper is to define alternative construction processes for a building with reinforced concrete slab floors, thereby estimating which ones are most beneficial in terms of their execution time and cost. Three alternatives were proposed to solve the deadlines of the construction process: Shoring and Striking; Shoring, Clearing and Striking; and Shoring, Reshoring and Striking, considering 2, 3 and 4 consecutive shored floors. In order to evaluate what processes are valid, first it is necessary to calculate the loads during the construction process using the New Simplified Procedure and subsequently check whether or not the striking condition is fulfilled in each of the construction operations. Regarding the studied building, the feasible construction processes were: Shoring, Clearing and Striking with 3 and 4 consecutive shored floors.